Synthesis of 2,2-Disubstituted and 2,2,3-Trisubstituted 1,4-Dioxane-Derived Building Blocks - Bondarenko, Andriy V.; Kozyriev, Yevhenii K.; Vashchenko, Bohdan V.; Grygorenko, Oleksandr O. (Synthesis, 2023)
An approach to the preparation of 2,2-disubstituted and 2,2,3-trisubstituted 1,4-dioxane-derived building blocks is described. The reaction sequence commenced from dimethyl- or spirocyclobutyl-substituted oxiranes bearing an additional benzyloxy group as the starting materials. The key step of the 1,4-dioxane ring construction included oxirane ring opening with ethylene glycol monolithium salt, followed by the two-step cyclization of the diols obtained. The utility of the method was demonstrated by multigram preparation (up to 300 g; 30 g average scale of the final products) of 2,2-dimethyl-1,4-dioxane and 5,8-dioxaspiro[3.5]nonane building blocks, i.e. carboxylic acids, alcohols, amines, aldehyde, ketones, and bromides. Additional synthetic possibilities were shown by the preparation of selected examples of 1,4-dioxane-containing acetylenes, thiols, sulfonyl halides, and sulfonamides.
Keywords: oxygen heterocycles; 1,4-dioxanes; building blocks; oxiranes; saturated compounds